2007
DOI: 10.1093/jpepsy/jsm067
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Taiwanese Infants' Mental and Motor Development 6 24 Months

Abstract: Differences existed in the mental and motor development among Taiwanese and American infants. Our preliminary norms of the BSID-II may be more appropriate than the United States norms for Taiwanese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 29 publications
0
40
2
2
Order By: Relevance
“…Other studies from the international neuropsychological community sought to determine the adequacy of published normative data and/or establish local normative data (Skuy et al 2001;Wu et al 2008). These authors employed large samples (≥200) and compared the observed performances of participants in their study to other published normative data as a means of demonstrating the inadequacy of established standards and the clinical need for local alternatives.…”
Section: Primary Findingsmentioning
confidence: 99%
“…Other studies from the international neuropsychological community sought to determine the adequacy of published normative data and/or establish local normative data (Skuy et al 2001;Wu et al 2008). These authors employed large samples (≥200) and compared the observed performances of participants in their study to other published normative data as a means of demonstrating the inadequacy of established standards and the clinical need for local alternatives.…”
Section: Primary Findingsmentioning
confidence: 99%
“…7,13,[25][26][27] Excluding the group of "teen mothers" who were younger than 16 years old at the time of giving birth and whose children failed the test, it could be said that, in general, an older maternal age had a direct effect on results, probably reflecting the limitations of time devoted to upbringing and/or fatigue with the maternal role. Both tendencies have been reported several times.…”
Section: Discussionmentioning
confidence: 99%
“…U n l i k e w h a t h a s b e e n r e p e t i t i v e l y reported, 4,6,7,[17][18][19][20][21]26 a significant association between socioeconomic status (measured as per SEL), children sex or age and the risk of failing the test was not verified, probably due to the sample's homogeneity, the small age range and the relative small sample size, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Estudios previos, controlados para variables socioeconómicas, ya habían informado el peso nocivo de la malnutrición sobre el nivel de desarrollo o el coeficiente intelectual (CI). 25,29 7,13,[25][26][27] Excluyendo al grupo de "niñas-madres" menores de 16 años al parir, cuyos hijos/as no pudieron pasar la prueba, puede decirse, en general, que el incremento de la edad materna afectó directamente el resultado, lo que quizá refleja limitaciones de tiempo para criar y/o desgaste de la función materna. Ambas tendencias ya fueron comunicadas en diversas oportunidades.…”
Section: F a C T O R E S D E R I E S G O P A R A S O S P E C H O S O unclassified
“…E n c o n t r a d e l o i n f o r m a d o c o n reiteración, 4,6,7,[17][18][19][20][21]26 no pudo comprobarse una asociación significativa entre las variables condición socioeconómica (medida con el NSE), edad del menor o género y el riesgo de no pasar la pesquisa, debido quizá a la homogeneidad de la muestra, el acotado rango etario y el relativo pequeño tamaño muestral, respectivamente.…”
Section: F a C T O R E S D E R I E S G O P A R A S O S P E C H O S O unclassified